Revision of the genus Diochus Erichson (Coleoptera: Staphylinidae, Staphylininae, Diochini) from Thailand and Myanmar - Huang, Tian; Janák, Jiří; Zhou, Hong-Zhang (Zootaxa, 2025)
The taxonomy of the genus Diochus Erichson, 1839 (Coleoptera: Staphylinidae, Staphylininae, Diochini) was studied in this paper. Six new species are described: Diochus crispus Huang, Janák & Zhou, sp. nov., D. robustus Huang, Janák & Zhou, sp. nov., D. umphangensis Huang, Janák & Zhou, sp. nov. and D. balangensis Huang, Janák & Zhou, sp. nov. from Thailand, D. bilobatus Huang, Janák & Zhou, sp. nov. from Thailand, India, China, Vietnam and Laos, and D. myanmarensis Huang, Janák & Zhou, sp. nov. from Myanmar. Eight previously described species are revised here: D. bisegmentatus Zhou & Zhou, 2016 is recorded from Thailand and Myanmar for the first time, D. caudapiscis Shuai, Nozaki & Tang, 2021 is recorded from Thailand for the first time, while data including diagnostic characters are provided for D. emarginatus Huang, Janák & Zhou, 2024, D. setatus Huang, Janák & Zhou, 2024, D. guizhouensis Shuai, Nozaki & Tang, 2021, D. conicollis (Motschulsky, 1858), D. punctipennis (Motschulsky, 1858), and D. antennatus (Motschulsky, 1858). A key to all 14 species is provided and all new and newly recorded species are illustrated.